Educational Values Presented in the English Translation of the Holy Quran Surah Luqman: A Qualitative Content Analysis - Irma Wahyuni (PUSAT SAINS INDONESIA, 2020)
This research utilizes qualitative-explorative design. As the qualitative study, it tries to presenting the analysis of content in the English translation of the Quran, specifically the educational values in Surah Luqman. The instrument of the research is document of the English translation of Surah Luqman by Abdullah Yusuf Ali, and the theory of education that is to “produce a good man” that had been stipulated in the First World Conference on Muslim Education organized in Jedda-Mecca (1393,A.H – 1977,A.D). Meanwhile triangulation employed as the data collecting technique including observation, documentation, and consulting to the expert. The researcher sum up that at least there are three categories of education in the English translation of Surah Luqman; spiritual education, character education, and social education. The way of how those categorizations are analyzed is presented. Further research discusses English translation of the Quran related to broader linguistic areas is recommended in order to develop the more comprehensive insight for researchers particularly those in education, english education, and linguistics.